Penerapan Metode Multi Objective Optimization on The Basic of Ratio Analysis (MOORA) pada Pemilihan Masker Organik Wajah Berdasarkan Kriteria - Ade Dwi Amanda; Fildzah Nadya Arieni; Agus Perdana Windarto (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Organic masks are masks made from natural ingredients that have good nutritional content for the face. Organic masks have many benefits which are certainly no less than treatments at a beauty doctor. Facial masks are beauty masks in the form of gels, pastes and powders which are applied to clean and tighten the skin, especially facial skin. Face masks also function as carriers for active ingredients that are useful for skin health, such as extra plants, essential oils, or seaweed that can be absorbed by the skin's surface to be carried into the blood circulation. The purpose of this study is to help consumers determine the best organic face mask. This research method uses the MOORA method. The criteria used are Variant (A), Size (B), Price (C), Aroma (D), Method of Use (E), Rules of Use (F), Results of Use (G). The alternatives used are Crushlicious (0.1147), Namo.Id (0.2758), NHM (0.2257), Lea Gloria (0.7218), Poupeepou (0.1692), and Natuna Oilvera (0.1157). Thus, the best value of the six alternatives is the Lea Gloria Organic Face Mask with a value of 0.7218.